2019
DOI: 10.1186/s40816-019-0145-8
|View full text |Cite
|
Sign up to set email alerts
|

Toxicological implications of the fruit of Harungana madagascariensis on wistar rats

Abstract: Background: The unopened buds of the fruit of Harungana madagascariensis is used in the treatment of anaemia and skin diseases in traditional medicine. Hence, this study aims to scientifically evaluate the effects of oral administration of the fruit extract of Harungana madagascariensis on haematological, biochemical and histological parameters in Wistar rats. Methods: Phytochemical screening of the ethanol fruit extract of H. madagascariensis was carried out. Acute toxicity test was done using Lorke's method.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 25 publications
0
6
0
Order By: Relevance
“…ex Poir Used to treat typhoid, diarrhea, anemia in Cameroun, skin diseases in Ghana, analgesic and treatment of toothache in Guinea, Chronic diarrhea in Tanzania and Rwanda. Used to treat asthma, tuberculosis and fever [ 192 , 193 ] Induced anti-HIV activity [194] The LD 50 of fruits was > 5000 mg/kg and long term use at high dose could induce toxicity [195] Hepatitis, meningitis, poliomyelitis Hygrophila auriculata (Schumach.) Used to treat jaundice and other hepatic obstruction, malaria.…”
Section: Discussionmentioning
confidence: 99%
“…ex Poir Used to treat typhoid, diarrhea, anemia in Cameroun, skin diseases in Ghana, analgesic and treatment of toothache in Guinea, Chronic diarrhea in Tanzania and Rwanda. Used to treat asthma, tuberculosis and fever [ 192 , 193 ] Induced anti-HIV activity [194] The LD 50 of fruits was > 5000 mg/kg and long term use at high dose could induce toxicity [195] Hepatitis, meningitis, poliomyelitis Hygrophila auriculata (Schumach.) Used to treat jaundice and other hepatic obstruction, malaria.…”
Section: Discussionmentioning
confidence: 99%
“…Although research has shown H. madagascariensis to be of high medicinal value, its prolonged usage in treating diseases has to be done with great caution, taking into account its potential toxic effect. Studies carried out by Shorinwa and Monsi (2020) on the toxicity of ethanol extract from the fruit of H. madagascariensis on Wistar rats showed inflammatory cells in the portal tract of the ethanol-treated rats. The level of inflammation was proportional to the dosage concentration and duration.…”
Section: Toxicitymentioning
confidence: 99%
“…Animal model experiments were performed in accordance with OECD guidelines 423 and 407 for toxicity assessment [25,26] and the previous methods with minor modifications [27][28][29][30][31][32]. Fifty-five laboratory albino rats aged 8 weeks were collected from Sokoine University of Agriculture (SUA).…”
Section: Experimental Animals and Dosesmentioning
confidence: 99%